2014
DOI: 10.1371/journal.pbio.1001770
|View full text |Cite
|
Sign up to set email alerts
|

Nonindustry-Sponsored Preclinical Studies on Statins Yield Greater Efficacy Estimates Than Industry-Sponsored Studies: A Meta-Analysis

Abstract: This study by Lisa Bero and colleagues uses published preclinical statin research to show that nonindustry-funded animal studies yield more efficacious drug results than do industry-funded ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 49 publications
1
31
0
Order By: Relevance
“…A previous analysis of preclinical studies of statins found a notable discordance between results and conclusions in industry‐sponsored studies compared with non‐industry‐sponsored studies 7. This discrepancy between results and conclusions has also been observed in meta‐analyses of randomized controlled trials and trials of drugs conducted in humans 2, 3.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A previous analysis of preclinical studies of statins found a notable discordance between results and conclusions in industry‐sponsored studies compared with non‐industry‐sponsored studies 7. This discrepancy between results and conclusions has also been observed in meta‐analyses of randomized controlled trials and trials of drugs conducted in humans 2, 3.…”
Section: Discussionmentioning
confidence: 95%
“…The Institute of Medicine (IOM) 2010 report on Conflicts of Interest in Medical Research, Education and Practice highlights the need for systematic reviews to reveal the extent of financial relationships and their consequences in preclinical research 6. One systematic review has found that, in contrast to clinical studies, industry‐sponsored preclinical studies underestimate effect sizes of the drugs being tested compared with non‐industry‐sponsored studies 7. Thus, industry sponsors may have different incentives that could influence the outcomes of clinical versus preclinical studies 8.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence indicated that industry-sponsored research is less biased than academic research [40]. We therefore predicted higher rates of reporting of measures against risks of bias in applications from private compared to academic institutions.…”
Section: Discussionmentioning
confidence: 96%
“…When a promising therapy fails in clinical trials there is an opportunity to critically evaluate flaws in the experimental model in the reverse translation approach: however, attempts at reverse translation have been rather limited. Explanations for failed translation that explore reasons beyond preclinical modeling have been advanced, including clinical trial design features, inconsistent test article application between nonclinical and clinical trials (dose, timing, and route), bias or selective reporting, and data interpretation Krauth et al, 2014).…”
Section: Why Are Some Models More Predictive Than Others?mentioning
confidence: 99%